Ecofriendly Synthesis of ZnO Nanoparticles using Zingiber Officinale and Syzygium Aromaticum Extracts for Antibacterial Applications - Tuama, M. J.; Alias, M. F. A. (Iraqi Journal of Science, 2024)
Zinc oxide nanoparticles (ZnO NPs)  were prepared by green method using Zingiber officinale (G-ZnO) and Syzygium aromaticum extract (S-ZnO). X-ray diffraction (XRD) investigations revealed that ZnO NPs have wurtzite hexagonal structures in extracts of Zingiber officinale and Syzygium aromaticum, with average crystal sizes of about 38.49 nm and 27.66 nm,   respectively. FTIR was performed to investigate the nature of functional groups in the active compounds responsible for the formation of ZnO NPs. The diffuse reflection spectroscopy (DRS) showed the direct bandgap energy of the as-prepared nanoparticles. The zinc oxide sample composition and purity  were confirmed using energy dispersive  X-ray spectroscopy (EDX). The morphological properties of ZnO NPs prepared from both plants were investigated using scanning electron microscopy (SEM). G-ZnO and S-ZnO nanoparticles appeared agglomerated of triangular, spherical and various other shapes, respectively. The average size of nanoparticles for  G-ZnO and S-ZnO NPs were  26.92 nm and 62.45 nm, respectively. In addition, the as-prepared ZnO NPs showed significant bactericidal effects against gram-positive and gram-negative pathogenic bacteria.